Building consumers’ confidence in adopting e-commerce: a Malaysian case - Ahmed, Mohiuddin; Hussein, Ramlah; Minakhatun, Rashidah; Islam, Rafikul (Inderscience, 2007)

(untitled)
Consumers’ confidence on the online transactions is vital for the continuous growth and development of electronic commerce. In the present study, we experimentally investigate the measures of consumers’ perceived security and privacy over online transactions as well as the perceived trust and reliability of online vendors in order to influence consumers’ overall confidence in e-commerce transactions. On the basis of responses from 163 participants, it is concluded that the major concerns in e-commerce adoption are: security and privacy over online transaction process and trust and reliability of online vendors. In order to be successful in electronic marketplace, the organisations are expected to expend their resources and exert efforts to ensure that consumers’ concerns are adequately addressed.